The Objections Educating Spirituality of Religious Education Students - Verbylaitė, Dalia (Acta Paedagogica Vilnensia, 2005)
The article presents the objections educating spirituality of religious education students. The most important objections are following: students’ attitudes to religious education purposes, the evaluation of religious studies at the university, the competencies of teachers and their spiritual maturity, students’ taking part in non-academic activities. More than a half of students among religious education purposes evaluate knowledge of religion, reflection of religious experience, search for meaning of life and love for people. Very negative evaluations students gave to these purposes: help of religious education entering parish community, feeling happy and free from various influences. Very good evaluations get these components of religious education: content - 86,8%, less percent – purposes of religious education, less than a half of students evaluate principles. About third and more students evaluate methods in educational process. More than a half of students positively evaluate teachers’ competences and spiritual maturity. There is students emotional and behaviour influence to teachers’ competences and spiritual maturity. 50,1 % students (without studies) participate in other activities. More then a half of them are very satisfied with those activities, less than a half are satisfied and 2% are not very well satisfied. Students participating in other activities understand better the essence of spirituality. It’s clear that students satisfaction with their own activities depends on their purposive of activities (r =0,254; p < 0,01 ): the more purposely they understand their own activities the more their satisfaction is bigger. There is correlation between students understanding of possible activities and their purposive of activities (r=0,462; p < 0,01): the more activities are purpose the more they the students see possibilities for them. So purposive of possible activities depends on essence of spirituality (r=0,182; p < 0,05).